Radial profile of the electron energy distribution function in RF capacitive gas-discharge plasma. (March 2016) - Dimitrova, M; Popov, Tsv; Puac, N; Skoro, N; Spasic, K; Malovic, G; Dias, F M; Petrovic, Z Lj
Abstract: This paper reports experimental results on low-pressure argon capacitive RF discharge (parallel-plate capacitively-coupled plasma - CCP) under different conditions, namely, gas pressure in the range 3 -r- 30 Pa and RF power in the range 10 - 100 W. The IV characteristics measured were processed by two different second-derivative probe techniques for determination of the plasma parameters and the electron energy distribution function. The radial profiles of the main plasma parameters are presented.